Electrical Characteristics of PN Junction Structure for GaAs, InP and InSb based III-V Compounds - Tin Tin Hla; Kyawt Khin; Hnin Ngwe Yee Pwint (AI Society & STMIK Indonesia, 2025)
The electrical properties of the pn junction structure for GaAs, InP and InSb based III-V compounds using the numerical equation are provided by a computer-aided simulation method. The band model predicts the electrical properties of III-V compound semiconductors. The analytical description of the immobile space charge layer (ISPL) related to immobile charge concentration, the amount of electric field intensity and the barrier potential height under unbiased, forward-biased and reverse-biased conditions has been investigated. And then the specific explanation of electron and hole distributions in the bulk region due to the majority carrier injection under forward biasing has been evaluated by using boundary conditions. The J-V characteristics of Group III-V compounds are observed using mathematical computation based on diffusion current density and recombination current density of the pn junction structure.